2014
DOI: 10.1111/apa.12602
|View full text |Cite
|
Sign up to set email alerts
|

Left‐behind children in rural China experience higher levels of anxiety and poorer living conditions

Abstract: LBC have a relatively higher level of social anxiety and poorer living conditions than non-LBC, and there are differences in social anxiety, and its relevant factors, between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 12 publications
7
83
0
Order By: Relevance
“…The observed relatively stronger effect of neglect was consistent with the result from an early study reporting the strongest influence of childhood neglect among various childhood adversities on adult personality pathology [77]. Being neglected in childhood might reflect a serious lack of care from close family members, most likely from own parents [12]. Such experiences at any point in childhood, especially in infancy, have a powerful and profound effect on the development of personality and life styles across the lifespan.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The observed relatively stronger effect of neglect was consistent with the result from an early study reporting the strongest influence of childhood neglect among various childhood adversities on adult personality pathology [77]. Being neglected in childhood might reflect a serious lack of care from close family members, most likely from own parents [12]. Such experiences at any point in childhood, especially in infancy, have a powerful and profound effect on the development of personality and life styles across the lifespan.…”
Section: Discussionsupporting
confidence: 84%
“…There are relatively less comprehensive reports on these problems from Asia. But in China, for instance, a large amount of children in rural areas has to live apart from their parents who strive in big cities for job opportunities, being left behind and to a certain degree neglected by their parents [12,13].…”
mentioning
confidence: 99%
“…Zhao et al (2014) found that LBC who completed the SASC, reported lower quality of life (QOL) and greater neglect and physical abuse, compared to non-LBC.…”
Section: Emotional and Behavior Problemsmentioning
confidence: 99%
“…Parental migration is found to be associated with loneliness [810], low self-esteem [11], depressive and anxiety symptoms [1114], risk behaviors [15], poor school performance and early dropout [1517]. Studies have reported that migration type (father-only, mother-only, or both-parent migration) and care arrangements [1820], as well as child age [21, 22] and sex [15, 23] were important correlates of LBC’s mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%